(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
The aim of this study was to evaluate a public program for smoking cessation based on guidelines of the National Cancer Institute (INCA). We evaluated 109 patients enrolled in a public hospital during the period of two years. The participants underwent four sessions of cognitive-behavioral group associated with nicotine replacement and bupropion. The maintenance of non smoking was evaluated one month, four months and six months after treatment. The results showed that 83.5% of the participants quit smoking after the treatment. After a month a few relapses occurred, but after four and six months the number of abstinent falls by almost half. The results show that cognitive-behavioral therapy combined with medication is effective in smoking cessation, reinforcing the importance and effectiveness of public programs for smoking cessation